2020
DOI: 10.1021/acsaem.0c00823
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Perovskite Solar Cells by One-Step Self-Assembled Perovskite-Polymer Thin Films

Abstract: Perovskite materials have drawn the greatest attention as alternatives for approaching cost-effective perovskite solar cells (PSCs) in the past decade. However, the desire for PSCs with photocurrent hysteresis-free characteristics has been unfulfilled due to the intrinsic foibles of perovskite materials. In this study, PSCs with boosted power conversion efficiency (PCEs), dramatically suppressed photocurrent hysteresis, and significantly boosted stability through one-step self-assembled methylammonium lead iod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
57
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 26 publications
(60 citation statements)
references
References 34 publications
3
57
0
Order By: Relevance
“…To our knowledge, the detectivity of device with 5% PEOXA addition is comparable to the best reported value of α‐CsPbI 3 based self‐powered photodiode. [ 31,23 ] Analogously, device with 5% of PEOXA addition exhibits the highest EQE value of 40% under 0 V bias. Comparison in efficiencies of the device under different bias voltages is shown in Figure 2e, manifesting a positive correlation of the EQE values with the bias voltage.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To our knowledge, the detectivity of device with 5% PEOXA addition is comparable to the best reported value of α‐CsPbI 3 based self‐powered photodiode. [ 31,23 ] Analogously, device with 5% of PEOXA addition exhibits the highest EQE value of 40% under 0 V bias. Comparison in efficiencies of the device under different bias voltages is shown in Figure 2e, manifesting a positive correlation of the EQE values with the bias voltage.…”
Section: Resultsmentioning
confidence: 99%
“…[27] Zheng et al further investigated high-performance perovskite photovoltaics by one-step self-assembled polymerperovskite thin film, achieving dramatically suppressed hysteresis and boosted stability. [23] Unfortunately, the quantity of researches on stable CsPbI 3 -based thin film photodetectors are relatively limited and somewhat unsatisfactory. [1,28] It has been reported that CsPbI 3 exists in different black phases, including cubic(α)-CsPbI 3 , orthorhombic(γ)-CsPbI 3 , and tetragonal(β)-CsPbI 3 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations